G-111 DNA prime/subunit boost using SIVE660 based rhFLSC yields 75% efficacy against cross clade SIVmac251 intrarectal challenge. (January 2016) - Fouts, Timothy; Prado, Ilia; Bobb, Kathryn; Schwartz, Jennifer; Bagley, Kenneth; Xu, Rong; Otya-Setlik, Ayuko; Egan, Michael; Eldridge, John; Montefiori, David; LaBranche, Celia; Pal, Ranajit; et al.
Abstract : An effective vaccine for HIV still remains elusive. Our previous studies showed that a protein-based FLSC (a genetic fusion of gp120 and CD4) protected macaques against repeat rectal challenges with SHIV162P3 but efficacy was low. We hypothesized that DNA would provide a superior prime to a subunit boost than subunit alone and that the adjuvants IL-12 and/or LTA1 would improve priming. FLSC delivery regimens were evaluated in a challenge model using SIVsmE543 antigens and a cross clade challenge with SIVmac251. Eight macaques/group were immunized with DNA expressing a gag/pol fusion and FLSC with/without LTA1, IL-12 or LTA1+IL-12 by electroporation on weeks 0, 4 and 8. Booster immunizations of 300 μg of FLSCsmCG7V/alum were given at week 42. Two weeks later, animals were weekly challenged rectally 10 times with SIVmac251. Immune measures were compared using T tests (parametric) or Mann-Whitney Rank Sum Tests (non-parametric). Infection rates were compared using Log Rank tests. The DNA/IL-12 prime regimen provided 75% efficacy compared to the same regimen without IL-12. Efficacy did not correlate with antibody binding or neutralizing titers to Tier 1 SIVmac251 whereas ADCC titers and antibody binding ratios of FcgR3/FcgR1 correlated with protection, provided T cell responses were low. The DNA/LTA1/IL-12 regimen generated substantially superior CMI responses, but showed no protection. These results suggest that vaccines generating ADCC capable antibodies with high FcgR3/FcgR1 ratios that evoke minimal T cell responses may be the most protective.